Oppression towards Women as Depicted in Marge Piercy’s Selected Poems - Diksita Galuh Nirwinastu (Universitas Sanata Dharma, 2021)
This present study would like to examine how women are oppressed by the patriarchal society in the selected poems written by one of the contemporary American female writers, Marge Piercy. Marge Piercy is particularly known as a female writer as well as a feminist activist. She has written numerous works, including novels and poetry books, which explore issues about women. Piercy’s poems are mostly known to be simple and vivid. Observing the use of figurative language and the diction in Piercy’s selected poems, entitled “A Work of Artifice” and “Barbie Doll”, in the light of feminist criticism, this article would like to show how oppression is done towards women and how it results in the silencing, shaping, and subordinating of women. In the poems, the oppression is mostly operated subtly and systematically through various cultural institutions, such as education, family, and media. Women, as a result, are trained to believe in the voice of the patriarchal society and to behave following what the patriarchal society demands. The long-practiced oppression has hindered women to develop to their fullest as human beings. The poems can be read as a medium to voice women’s experiences and to criticize the established patriarchal system and its oppression towards women.